Tendințe în evoluția sistemelor fiscale ale țărilor membre ale OCDE, UE și România - Văcărel, Iulian (Calitatea Vieții, 2007)
In the beginning, this article briefly presents the general evolution of fiscal policies, during the XX-th century, within different countries. Enhancing the historical importance that regional organizations have had in orienting the countries’ fiscal policies, during the second half of the XX-th century, the author largely describes those policies and their evolution, in the next three chapters. Thus, it is presented the evolution of fiscal policies in the member-states of: OECD, EU for the reminded period, than the same analysis is made in the case of Romania, in the beginning of its EU integration. The conclusions presents personal opinions of the author regarding the budgetary- fiscal system of Romania, in the new context – Romania as EU country,trough several proposals and analyses.